Sustaining Innovation Capabilities Beyond COVID - Janet Erin Zlotnik; Thomas Carey (Journal of Innovation in Polytechnic Education)
The innovation achievements and momentum of the COVID-19 pandemic present an opportunity for Canadian polytechnics to sustain their unique and distinctive role in the post-secondary landscape. The authors contend that if polytechnics collaborate with workplace partners to research and to advance Employee-led Workplace Innovation capabilities, polytechnics can better equip learners for the future of work, foster innovation in the workplaces of partners, and contribute meaningfully to innovation-based growth in Canada. Drawing on Breznitz’ critique, the authors advance the idea that Canadian innovation will grow if it focuses on ‘agents of innovation’, specifically the individual. Then the paper briefly outlines the traits of individual ‘serial innovators’ before honing in on the research and the work underway globally in the area of Employee-led Workplace Innovation. After establishing its value, the authors contend that if the work of polytechnics is to continue to have relevance for industry and to be differentiated from other types of post-secondary institutions, then the integration of Employee-led Workplace Innovation can play a key role. Its successful integration, however, requires an epistemological shift from the status quo, a shift which is described by way of a historical analogue and an example of curricular implications. The authors then explore the opportunity to build instructional capability for innovation in polytechnics themselves, both as a way to improve learning and as topic in its own right. Finally, the paper concludes with a summary of the opportunity polytechnics now have to sustain and possibly to evolve their unique role in strategic workforce development.